2016
DOI: 10.1039/c6cp02762h
|View full text |Cite
|
Sign up to set email alerts
|

Reactive force field development for magnesium chloride hydrates and its application for seasonal heat storage

Abstract: MgCl2 hydrates are considered as high-potential candidates for seasonal heat storage materials. These materials have high storage capacity and fast dehydration kinetics. However, as a side reaction to dehydration, hydrolysis may occur. Hydrolysis is an irreversible reaction, which produces HCl gas thus affecting the durability of heat storage systems. In this study, we present the parameterization of a reactive force field (ReaxFF) for MgCl2 hydrates to study the dehydration and hydrolysis kinetics of MgCl2·H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…59 The proton transfer is an important step in the hydrolysis of chloride-based hydrates. 34 To quantify the comparative hydrolysis resistance among MgCl 2 and CaCl 2 hydrates, we have calculated the enthalpy change in proton removal for CaCl 2 ·2H 2 O and MgCl 2 ·2H 2 O. The enthalpy change is obtained by gradually increasing the O–H interatomic distance.…”
Section: Resultsmentioning
confidence: 99%
“…59 The proton transfer is an important step in the hydrolysis of chloride-based hydrates. 34 To quantify the comparative hydrolysis resistance among MgCl 2 and CaCl 2 hydrates, we have calculated the enthalpy change in proton removal for CaCl 2 ·2H 2 O and MgCl 2 ·2H 2 O. The enthalpy change is obtained by gradually increasing the O–H interatomic distance.…”
Section: Resultsmentioning
confidence: 99%
“…ReaxFF MD is known to capture the physical and chemical phenomena under various conditions [18,26]. We have chosen various force fields for Pt/Ni and Si/SiO 2 systems, which can mimic their material properties.…”
Section: Discussionmentioning
confidence: 99%
“…37 ReaxFF, proposed by van Duin et al 21 in 2001 and continuously improved by Senftle et al, 38 is widely applied in the study of STSMs. 36,37,[39][40][41][42] It describes the interaction between atoms in the molecule system by BO. According to the electronegativity equilibrium theory (EEM), it renews the charge distribution around the atoms in the model.…”
Section: Reaction Force Fieldmentioning
confidence: 99%
“…They found the increase the concentration of HCl could inhibit the occurrence of proton transfer and thus inhibit the hydrolysis reaction, which was consistent with the conclusion of le Chatelier's principle. Since then, Pathak et al 40 studied the hydrolysis reaction of MgCl 2 Á 2H 2 O. The DFT simulation results showed that the barrier of the proton transfer was 19.55 kcal Á mol -1 .…”
Section: Reaction Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation